2021
DOI: 10.3389/fpsyt.2021.686177
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Internet Addiction Disorder and Its Correlates Among Clinically Stable Adolescents With Psychiatric Disorders in China During the COVID-19 Outbreak

Abstract: Background: Since the Coronavirus disease 2019 (COVID-19) pandemic emerged, Internet usage has increased among adolescents. Due to this trend, the prevalence of Internet addiction disorder (IAD) may have increased within this group. This study examined the prevalence of IAD and its correlates among clinically stable adolescents with psychiatric disorders in China during the COVID-19 outbreak.Method: A multi-center, cross-sectional study was carried out between April 29 and June 9, 2020 in three major tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…To date, although a few studies have examined internet use and smartphone use in adolescents, middle and high school students (17)(18)(19)(20)(21)(22), few studies examined the smartphone use pattern and PMPU among university students in China during the COVID-19 pandemic. Furthermore, no studies have examined the association between PMPU and life satisfaction using standard structured instruments.…”
Section: Introductionmentioning
confidence: 99%
“…To date, although a few studies have examined internet use and smartphone use in adolescents, middle and high school students (17)(18)(19)(20)(21)(22), few studies examined the smartphone use pattern and PMPU among university students in China during the COVID-19 pandemic. Furthermore, no studies have examined the association between PMPU and life satisfaction using standard structured instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the prevalence rate of IA symptoms in our study was approximately 1.5 times the rates reported in adolescents with MDD during an initial assessment in a Turkish outpatient clinic (30%) ( 25 ) and in clinically stable adolescents with MDD in China (36.9%) ( 2 ). The discrepancy could be attributed to patient characteristics.…”
Section: Discussionmentioning
confidence: 42%
“…Internet addiction (IA) generally refers to the behaviors of uncontrolled and persistent use of the internet, which can lead to individuals’ distress and social avoidance ( 1 ). IA symptoms are prevalent among adolescents and have received extensive attention from researchers around the world ( 2 4 ). A systematic review and meta-analysis reported that the prevalence rate of IA symptoms ranged from 0.6 to 50% worldwide, with a pooled prevalence of 2.0% in children and adolescents ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether some internet activities may be more addictive or detrimental to good sleep and a healthy lifestyle than others is an open question [ 181 ]. Increases in digital addiction during the COVID-19 pandemic, related to financial hardship, bereavement, isolation, anxiety, and stress, were reported in studies from different countries [ 66 , 182 , 183 , 184 ]. This further prompts our awareness towards recognizing a new worldwide syndrome fueled by increasingly adverse societal conditions.…”
Section: Discussionmentioning
confidence: 99%